2015
DOI: 10.1039/c5nr04740d
|View full text |Cite
|
Sign up to set email alerts
|

Strong and superplastic nanoglass

Abstract: The strength-ductility tradeoff has been a common long-standing dilemma in materials science. For example, superplasticity with a tradeoff in strength has been reported for Cu50Zr50 nanoglass (NG) with grain sizes below 5 nm. Here we report an improvement in strength without sacrificing superplasticity in Cu50Zr50 NG by using a bimodal grain size distribution. Our results reveal that large grains impart high strength, which is in striking contrast to the physical origin of the improvement in strength reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Plastic flow then will take place in other sites, resulting in significant global plastic strain (Fig.4c). As a consequence, the existence of a large number of GGIs in the nanoglass benefits for the nucleation and the subsequent multiplication of shear bands while the metallic glass is shear band nucleation starved in samples of small sizes [4,[30][31][32]. As is observed above in the experimental section, the transition of deformation mode in nanoglasses might occur at a smaller size scale (~ 100 nm).…”
mentioning
confidence: 68%
“…Plastic flow then will take place in other sites, resulting in significant global plastic strain (Fig.4c). As a consequence, the existence of a large number of GGIs in the nanoglass benefits for the nucleation and the subsequent multiplication of shear bands while the metallic glass is shear band nucleation starved in samples of small sizes [4,[30][31][32]. As is observed above in the experimental section, the transition of deformation mode in nanoglasses might occur at a smaller size scale (~ 100 nm).…”
mentioning
confidence: 68%
“…Adibi et al [19] investigated the effect of the glassy grain size and found that, with the decrease of the grain size, the deformation mode changes from a single SB to uniform superplastic flow. Softening towards the NG occurs during superplastic flow, so Sha et al [20] proposed a bimodal grain size model, which could improve the strength without sacrificing super-plasticity. Besides the attractive mechanical properties, NG exhibits enhanced thermal stability compared with MG (Metallic glass) [21,22], attributed to the lower free energy state of NG compared with MG [23].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, it has been found that a Fe 90 Sc 10 nanoglass is ferromagnetic at 300 K, whereas the corresponding melt-quenched glass is paramagnetic, and only exhibits ferromagnetic order at a temperature below 200 K [5]. Moreover, nanoglasses have been reported to be more ductile, more biocompatible, and catalytically more active compared to the corresponding melt-quenched glasses [6][7][8][9][10][11][12][13][14]. Hence, by modifying the microstructure of nanoglasses using controlling the size of the amorphous grains (i.e.…”
mentioning
confidence: 99%